(untitled) (Veterinary Science, 2020)
The objective of the present study was to characterize certain parameters of goat production of Chicał-Co area, in the West of the La Pampa province, Argentina, using the EPO 2005, a structured survey of descriptive-exploratory type on some variables that have impact on the production model was conducted. The 165 farms in the area were evaluated, finding a predominance of flocks ranging from 101- 200 goats. Likewise, the male female ratio was found to be 1:46.6, being the average age of first service of 6,5±0,2 months and the percentage of replacement goats of 16.8 percent. Although it was developed in an arid region, the lack of water and pasture are not seen as limiting problems in the production system. It is concluded that, due to the level of animal existence, goat establishments in Chical-Co are considered small holder farmers or smallholders and despite the low ratio male:female, fertility level was good . On the other hand, the percentage of existing replacement goats in such establishments guarantees a good level of substitution of old females. In addition, the lack of pasture and water are not considered to be relevant problems of negative impact on goat production systems.